Measuring optimal ultrasound speed using endoscopic ultrasound in patients with chronic pancreatitis, including early stage. Issue 6 (6th April 2022) - Minaguchi, Takahito; Yamamiya, Akira; Tominaga, Keiichi; Kashima, Ken; Kunogi, Yasuhito; Sakuma, Fumi; Fukushi, Koh; Nagashima, Kazunori; Izawa, Naoya; Yamabe, Akane; Hoshi, Koki; Iijima, Makoto; et al.
: Objectives: Ultrasound speed (USS) correction improves image quality by estimating the optimal USS correcting the deviation from a predetermined USS. This study assessed USS differences between chronic pancreatitis (CP), early CP (ECP), and normal pancreas when using endoscopic ultrasound (EUS). The usefulness of measuring optimal USS was evaluated for patients with CP, including early stage patients. Methods: This study enrolled 116 consecutive patients for whom USS was measured using an EUS system. The USS correction principle is generation of a B‐mode image by changing the USS in all ranges while correcting the delay in the received data. Final diagnoses were made according to the Japanese diagnostic criteria for CP in 2019. They were classified as CP, ECP, or normal. We compared USS applied for these three groups. Results: The medians and ranges of USS values for patients in the normal, ECP, and CP groups were 1506.0 (1407–1600) m/s, 1580.0 (1520–1630) m/s, and 1574.0 (1537–1610) m/s, respectively. The USS values of the ECP and CP groups were significantly higher than those of the normal group ( P <  0.001). Analyses of the receiver operating characteristic curve in the normal pancreas, ECP, and CP revealed the area as 0.957, with specificity and sensitivity of 95.9% and 87.5%, respectively, using the USS of 1535 m/s as a cut‐off. Conclusion: Measurement of USS might be particularly useful for distinguishing between normal and ECP imaging.